Entropy-based Evaluation Method of Design Scheme for Helicopter Transmission - Wang Haiwei; Liu Geng; Yang Zhanduo; Wei Zhongsheng (Institute of Advanced Engineering and Science, 2013)
To choose the best design scheme of helicopter transmission, and bring out excellent comprehensive performance for helicopter, technical criteria architecture of helicopter transmission is analyzed. Scheme criteria evaluation matrix is standardized and criteria weight vector of every design scheme is optimized. According to the principle of minimum deviation of design scheme evaluation, single scheme evaluation problem is programmed. Uncertainty factors of criteria weight are analyzed, and entropy is introduced to describe these uncertainties. In addition to the maximum entropy theory, an evaluation model of design schemes is formed, which is solved by constructing a Lagrange function and a nonlinear system of equations. The example demonstrates validity of the proposed evaluation method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2701